Expanding the Teaching Commons: Making the Case for a New Perspective on SoTL - Kim A. Case, PhD (Park University, 2013)
As a reflection on O'Meara, Terosky, and Neumann's (2011) work on scholarship of teaching and learning (SoTL) faculty development, this essay describes the benefits of SoTL to individual faculty and university goals. In support and expansion of arguments advanced by O'Meara et al., this work calls for the use of SoTL faculty development to promote the shared teaching commons, active recruitment of new SoTL scholars, institutionalization of SoTL values, and integration of SoTL initiatives in both teaching centers and research-focused development offices.